The effect of first trimester body mass index on the changes in the upper lip bite test classification before and after delivery: A prospective observational study - Li, Yannan; Li, Yue; Chen, Qufei; Hua, Hanli; Jiao, Jing; Zhang, Le; Chen, Liming; Huang, Shaoqiang (Frontiers in Medicine, 2022)
Background: The difficult airway (DA) assessment and management of pregnant woman has always brought specific challenges. The aim of this study was to investigate the effect of labour on the airway by assessing changes in the upper lip bite test (ULBT) classes and to explore its correlation with the first trimester's body mass index (BMI). Methods: According to the BMI of the first trimester, 354 full-term women were divided into low BMI group, normal BMI group and high BMI group. The ULBT class and pregnancy outcome were recorded and compared at early labour, after delivery, and 48h after delivery. Results: The ULBT class was increased in 75(21.1%) patients after delivery. Compared to the normal BMI group, the high BMI group had a higher probability of increasing (34.8% vs. 17.5%; P=0.002). The number of women with ULBT class 2~3 increased to 157, which was 1.48 times that of early labor. The number of women with ULBT class 3 increased from 4 to 16, of which 7 (53.8%) were from the high BMI group. Binary logistic regression analysis showed that first trimester’s BMI was associated with a significant increase in ULBT class after delivery (adjusted odds ratio [aOR]=2.13 [0.91-4.98], P=0.02). The ULBT classes of the three groups tended to return to their initial level 48h after delivery (P>0.05). Conclusion: Labor results in an approximately one-fifth increase in ULBT class. Being overweight or obese in the first trimester is associated with an increased risk of DA during labor.